2008
DOI: 10.1271/bbb.70645
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofRosa rugosaPetals on Intestinal Bacteria

Abstract: The effects of pulverized petal of Rosa rugosa on the growth of 10 species of intestinal and pathogenic bacteria were investigated. Growth of bifidobacteria and lactobacilli was not affected by the addition of the petal in plate cultivation. However, the growth of Bacteroides vulgatus, Escherichia coli, Staphylococcus aureus, and Bacillus cereus was completely inhibited by the addition of 0.1, 0.5, 0.1, and 0.05% (w/v) of the petal respectively. In liquid cultivation, the addition of the petal (0.5%) stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…However, this astringent property is also responsible for their antidiarrheal action which may be valued in some circumstances. Moreover, significant antioxidant, antibacterial, antimutagenic effects of tannins are known [12]. The tannin content in teas was determinated using the modified pharmacopoeial method [16].…”
Section: Determination Of Tannin Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this astringent property is also responsible for their antidiarrheal action which may be valued in some circumstances. Moreover, significant antioxidant, antibacterial, antimutagenic effects of tannins are known [12]. The tannin content in teas was determinated using the modified pharmacopoeial method [16].…”
Section: Determination Of Tannin Contentmentioning
confidence: 99%
“…gallic acid, ellagic acid), o-dihydroxyphenols (e.g. caffeic acid) and hydrolysable tannins in various R. rugosa parts [1,8,12,32]. These compounds possess proven cytotoxic, antimicrobial and antioxidant activity [8,12,30].…”
Section: Correlation Between Antiradical Anticancer and Antibacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Very limited studies reported certain growth stimulation of medicinal plants and bioactive compounds on intestinal microbiota. Haedanghwa (Rosa rugosa) petals promoted the growth of B. breve, but the growth of pathogenic bacteria was inhibited by nearly 50% (30). Accordingly, 1,4-and 1,8-dihydroxyanthraquinones from sickle pod exhibited strong growth-promoting activity on B. bifidum, but inhibited the growth of C. perfringens (31).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported apoptotic effect on HL-60 cells, antiinflammatory activity of casuarinin (9) (Yang et al 2000;Pan et al 2000), anti-dementia activity of tellimagradin II (6) and pentagallolylglucose (3) extracted from Sanguisorbae Radix (Lee et al 2005), anti-diabetic activity of pentagallolylglucose (3) extracted from Paeonia lactiflora roots (Baumgartner et al 2010), anti-oxidation activity of casuarinin (9) extracted from Terminalia arjuna (Chen et al 2004) and T. chebula (Cheng et al 2003), anti-oxidation and antitumor activities of pentagallolylglucose (3) (Okuda et al 2009), antibacterial activity of tellimagradin II (6) extracted from Rosa rugosa (Kamijo et al 2008), antioxidant activity and DPPH radical-scavenging activity of pedunculagin (5), casuarictin (4) and casuarinin (9) isolated from walnuts (Juglans regia L.), and preventive effect on liver damage induced by carbon tetrachloride of tellimagrandin II (6) and casuarictin (4) isolated from walnuts (J. regia L.) (Fukuda et al 2003;Shimoda et al 2008). Inhibitory effects of apple condensed tannins on compound 48/80-induced mast cell degranulation (Tokura et al 2005) and on histamine release from RBL cells (Kanda et al 1998) were reported.…”
Section: Introductionmentioning
confidence: 99%